ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN ACCOUNT OFFICER PADA PERSETUJUAN PERMOHONAN PEMBIAYAAN KONSUMTIF DI PT BANK SUMUT KCP SYARIAH HM JONI - Diah Hafni Pardede; Waizul Qarni; Ahmad Syukri (CV. Barokah Publsiher, 2023)
Financing analysis has a very important role for Islamic banks in making decisions regarding the approval or rejection of financing applications, as well as being a guide for Islamic banks in ensuring the validity of the application. In carrying out banking financial activities, account officers always have to analyze prospective customers to process the financing provided. Therefore, the role of account officers in Islamic banks is crucial. This study serves to analyze the factors that will influence the account officer's decision to approve the application for consumer financing, as well as the factors that are the reasons for the rejection of financing applications by customers at PT Bank Sumut KCP Syariah HM Joni. The method applied in this study is qualitative method, which is a method that does not focus on numbers but uses notes, observations, interviews, and documents. Data collection is carried out through literature studies, interviews, observations, and using primary and secondary data. From the results of research and discussion, it can be concluded that account officers must objectively evaluate various aspects related to financial subjects (Analysis 5C) before providing financing to customers who plan to apply for consumer financing at Bank Sumut KCP Syariah HM Joni.